2001
DOI: 10.1152/ajpgi.2001.280.2.g308
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase: expression in rat parietal cells

Abstract: Nitric oxide synthases (NOS) are enzymes that catalyze the generation of nitric oxide (NO) from L-arginine and require nicotinamide adenine dinucleotide phosphate (NADPH) as a cofactor. At least three isoforms of NOS have been identified: neuronal NOS (nNOS or NOS I), inducible NOS (iNOS or NOS II), and endothelial NOS (eNOS or NOS II). Recent studies implicate NO in the regulation of gastric acid secretion. The aim of the present study was to localize the cellular distribution and characterize the isoform of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Nonetheless, neurons are not the only source of these bioactive molecules. There is also a large amount of nonneuronal 5-HT and NO in the gastric mucosa itself (4,30,31), and we feel that the physiological roles for those molecules in the stomach have not been clearly identified yet. This present report suggests that gastric nonneuronal 5-HT and NO can act in the stomach mucosa as paracrine substances as well after the recognition of nutrients, such as an amino acid like glutamate, in a process similar to the one reported for the duodenal glucose sensing (47).…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, neurons are not the only source of these bioactive molecules. There is also a large amount of nonneuronal 5-HT and NO in the gastric mucosa itself (4,30,31), and we feel that the physiological roles for those molecules in the stomach have not been clearly identified yet. This present report suggests that gastric nonneuronal 5-HT and NO can act in the stomach mucosa as paracrine substances as well after the recognition of nutrients, such as an amino acid like glutamate, in a process similar to the one reported for the duodenal glucose sensing (47).…”
Section: Discussionmentioning
confidence: 94%
“…The constitutive form is calcium/calmodulin dependent and implicates the endothelial (eNOS) and neuronal (nNOS) isoform [46]. The expression of nNOS in rat gastric parietal cells was confirmed by Premarante by NADPH-diaphorase histochemistry, nNOS immunostaining, Western blotting and RT-PCR and published in 2001 [47]. However, the technique used for this study differs from our: they used immuno-dissected glands whereas we used hand dissected glands.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of studies on chloride secretion and changes in short-circuit current in the isolated rat distal colon, King et al (2004) suggested that NO is a secretomotor neurotransmitter in response to serotonin. Expression of nNOS in parietal cells suggests a participation of endogenous NO in the regulation of gastric acid secretion (Premaratne et al, 2001). Helicobacter pylori increased pepsinogen secretion from dispersed human peptic cells through a Ca 2ϩ -and NO-mediated intracellular pathway (Lorente et al, 2002).…”
Section: Secretion and Neurogenic Nitric Oxidementioning
confidence: 99%